Metadata and semantics research : 11th International Conference, MTSR 2017, Tallinn, Estonia, November 28 - December 1, 2017, Proceedings /: 11th International Conference, MTSR 2017, Tallinn, Estonia, November 28 - December 1, 2017, Proceedings. (2017) - Unknown
No abstract available